(untitled) (PANGEEA, 2025)
Natural rivers and man-made canals are open channels. They have many advantages over pipes and have been used for many centuries for water supply, for transport and for agriculture. [1] Critical and normal depth are two essential factors to consider when designing open channels. In trapezoidal channels, the governing equations are nonlinear for the normal and critical flow depths and thus the solution of the implicit equations involves numerical methods such as iterative ones (trial and error) and graphic methods. The complexity of equations often leads to an elevated risk of errors. A Python-based algorithm has been presented for the computation of uniform flow in open channels. This algorithm has the aim of enhancing students’ comprehension of the subject matter and offers greater accuracy through automated iteration-solving. The algorithm’s precision has been confirmed through a basic scenario, and its applicability is intended to extend to a broader range of channel shapes and flow conditions.